PELATIHAN TEKNOLOGI TEPAT GUNA DI KABUPATEN BANYUWANGI - Catur Pramono Adi (JURNAL KASTARA, 2023)
It was recorded that up to 2014 there were 71 marine and fisheries technologies that had been recommended but had not been optimally implemented by the community. One of the factors causing this condition is the limited outreach or dissemination of technology to assistants for marine and fisheries business actors which include extension workers, technicians, and lecturers. With the above problems, BRSDM KP is making efforts to synergize between the Research Center for Socio-Economic Maritime Affairs and Fisheries to synergize with specialized work units within the scope of BRSDM KP to carry out innovative and adaptive technology dissemination activities through Appropriate Technology Training activities. The purpose of this activity is to increase the competence of extension officers, widyaiswara and marine and fisheries instructors so that they have a productive, skilled, creative, disciplined, professional work ethic and are able to utilize, develop and master innovative and adaptive technologies. On the results of the evaluation of the implementation of technical guidance, discussions, and fieldwork Based on presentations, discussions, and field visits, some conclusions that can be formulated are: a). Participants thought that this activity was beneficial for increasing knowledge and knowledge, especially technology which was the material for technical guidance. It is hoped that this can also be continued for similar activities by increasing the aspect of identifying adaptive technology needs at the location; and b). The knowledge of the participants increased in various ways. This must be adjusted to the participants' various educational and occupational backgrounds (there are capture fisheries, there is aquaculture) in accordance with the fishery potential in their working area and the material.